AN ECONOMIC VISION OF THE CORRUPTION PHENOMENON IN PERU - Huarag Guerrero, Enrico Marcel (2020)
Corruption is a complex phenomenon that has been faced only from a traditional perspective, ignoring the economic incentives involved in its greatest incidence. The result of the measures adopted by the State has been quite disappointing, and inefficient in terms of reducing the incidenceof corruption acts. This essay aims to address the problem from an economic perspective, based on the approaches of the Public Choice Theory andthe New institutionalism. Thus, we will address the way in which economic incentives are aligned in the conduct of corrupt and corruptors, bureaucrats, candidates and voters. Finally, some measures are proposed to reduce the incidence of acts of corruption, considering the aforementioned approaches.Corruption – Law and Economics - Public Choice - Rational Ignorance - Incentives